2019
DOI: 10.1039/c8na00251g
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of hexagonal boron nitride impurities in boron nitride nanotubes via FTIR spectroscopy

Abstract: Preparation of high-quality boron nitride nanotubes (BNNTs) from commercially available stock is critical for eventual industry adoption and to perform comprehensive experimental studies of BNNTs. Separation of hexagonal boron nitride (h-BN) and BNNTs is a significant challenge, and equally so, quantification of h-BN content in mixed samples is a major challenge due to their nearly identical properties. This work introduces a simple method of quantifying h-BN content in BNNTs based on FTIR analysis. Quantifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 27 publications
4
50
0
Order By: Relevance
“…BNNT purification processes that we conducted are shown in Figure 1. Since amorphous boron is oxidized to B2O3 and boric acid during this process, the sample color changed from gray to white, as shown in Figure 2B [18]. These impurities could be removed by washing the sample with hot water or methanol.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…BNNT purification processes that we conducted are shown in Figure 1. Since amorphous boron is oxidized to B2O3 and boric acid during this process, the sample color changed from gray to white, as shown in Figure 2B [18]. These impurities could be removed by washing the sample with hot water or methanol.…”
Section: Resultsmentioning
confidence: 99%
“…The remained impurities are mainly h-BN particles with various sizes, which are difficult to separate from BNNTs because of their similar chemical properties. Recently, it was reported that h-BN impurities could be selectively removed by ultrasonically assisted diffusion separation [18,30]. The BNNTs and h-BN particles were dispersed in water by ultrasonication for 10 min, and the solution was vigorously stirred for 1 hr at 1400 rpm and filtered using a porous membrane (Stainless Steel Woven Wire Mesh) with 35 micrometer pore size.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it was recognized that there was a layer of water molecules in the presence of surfactant located adjacent to BNNTs, while surfactant's hydrophobic and hydrophilic segments were placed, distantly. In addition to MD simulation, it has been proven that Triton X-100 could produce slightly higher BNNT enrichment than cause the dispersion of BNNTs in experimental analysis [69]. The encapsulation of the dopamine and caffeine within (14,0) BNNTs was investigated by García-Toral et al applying MD simulation and DFT calculations.…”
Section: Theoretical Investigationsmentioning
confidence: 99%